Esthetic Crown Lengthening Associated With Modified Lip Repositioning Surgery (Modified LipStat) in the Treatment of Excessive Gingival Display: A 6-Year Follow-Up Case Report - Cesar Augusto Signori Arruda; Luciano Melo Pratto; Estevo D’Agostini Derech; Guenther Schuldt Filho (Case Reports in Dentistry)
Smiling expresses emotions and affects interpersonal relationships, influencing self-esteem and social life. Nowadays, concerns about aesthetics and access to the Internet have made people more informed and demanding about treatments for gingival smile. Excessive gingival display (EGD) is caused by a variety of factors that can act alone or in combination. These factors may include altered passive eruption (APE), vertical maxillary excess, a short upper lip, and hyperactive upper lip, among other factors that cause gingival hyperplasia. In this case report, the EGD was caused by vertical maxillary excess, hypermobility of the upper lip, and APE. The proposed treatment included two procedures: the Modified Lip Repositioning Surgery (Modified LipStat) Technique, with internal sutures to attempt to restrict the traction of the upper lip elevator muscles, and Esthetic Crown Lengthening (ECL) from the right first premolar to the left first premolar for the treatment of APE. The result provided an aesthetic improvement of the smile, with harmonization in relation to the size of the teeth. The mobility of the upper lip in spontaneous smiles remained reduced up to 6 months of follow-up; however, there was a partial relapse in the position of the upper lip during spontaneous smiling at the end of 6 years of follow-up.